Comparative Genetic Characterization of CTX-M-Producing Escherichia coli Isolated from Humans and Pigs with Diarrhea in Korea Using Next-Generation Sequencing - Kwang-Won Seo; Kyung-Hyo Do; Wan-Kyu Lee (Microorganisms, 2023)
Pathogenic E. coli causes intra- and extraintestinal diseases in humans and pigs and third-generation cephalosporins are the primary option for the treatment of these diseases. The objective of this study was to investigate the characteristics and correlation between CTX-M-producing E. coli from humans and pigs regarding CTX-M-producing E. coli using next-generation sequencing and bioinformatic tools. Among the 24 CTX-M–producing E. coli, three types of CTX-M genes (CTX-M-12, CTX-M-14, and CTX-M-15) were detected in humans and four types of CTX-M genes (CTX-M-14, CTX-M-15, CTX-M-55, and CTX-M-101) were detected in pigs. A total of 24 CTX-M–producing E. coli isolates also showed the following antimicrobial resistance genes: other B-Lactam resistance gene (75.0%); aminoglycoside resistance genes (75.0%); phenicol resistance genes (70.8%); tetracycline resistance genes (70.8%); sulfonamide resistance genes (66.7%); quinolone resistance genes (62.5%); trimethoprim resistance genes (54.2%); and fosfomycin resistance genes (8.3%). FII (92.3%) and FIB (90.9%) were the most common plasmid replicon in humans and pigs, respectively. A total of thirty-eight different genes associated with virulence 24 CTX-M–producing E. coli and all isolates contained at least more than one virulence gene. A total of 24 CTX-M–producing E. coli isolates showed 15 diverse sequence types (STs): thirteen isolates from human belonged to 6 different STs, and 11 isolates from pig belonged to 9 different STs. The presence of virulence genes in E. coli together with antimicrobial resistance genes (including CTX-M genes) emphasizes the necessity of comprehensive surveillance and persistent monitoring of the food chain to avoid all types of bacterial contamination, regardless of human or pig origin.